Calcaneoplasty coupled with an insertional Achilles tendon reattachment procedure for the prevention of secondary calcaneal impingement: a retrospective study. (August 2020) - Pi, Yanbin; Hu, Yuelin; Guo, Qinwei; Jiang, Dong; Xie, Xin; Zhao, Feng; Chen, Linxin; Ao, Yingfang; Jiao, Chen
Background: Posterior heel pain may occur after an Achilles insertional rupture reattachment procedure and could be attributed to an impingement between the calcaneal tuberosity and Achilles tendon, which could be observed using postoperative magnetic resonance imaging (MRI). Moreover, such impingement, which may be associated with postoperative pain symptoms, could be relieved by calcaneoplasty. Methods: Postoperative Visual Analog Pain Scale (VAS), American Orthopedic Foot and Ankle Society (AOFAS) score, Foot Function Index (FFI), Ankle Activity Score (AAS), and Tegner score were obtained and compared between 10 patients who underwent calcaneoplasty (calcaneoplasty group) and 11 patients who did not receive calcaneoplasty (non-calcaneoplasty group). Several signs of calcaneal tuberosity impingement identified in MRI were also compared between the two groups, which included retrocalcaneal bursitis, postoperative tendinopathy, tendon calcification, bone marrow edema, increased Achilles tendon diameter, and bony spurs. Results: The VAS score was 2.00 ± 1.41 and 2.18 ± 1.83 ( p  = 0.803), the AOFAS score was 90.60 ± 4.22 and 81.82 ± 7.77 ( p  = 0.005), the FFI was 5.00 ± 2.86 and 17.18 ± 15.92 ( p  = 0.028), the AAS was 5.50 ± 2.55 and 5.82 ± 2.04 ( p  = 0.750), and the Tegner score was 4.30 ± 1.49 and 4.45 ± 1.21 ( p  = 0.797) in the calcaneoplasty and non-calcaneoplasty groups, respectively. The AOFAS score and FFI were significantly different between the groups. MRI findings revealed that the non-calcaneoplasty group had significant signs of calcaneal impingement compared with the calcaneoplasty group. Conclusions: Secondary calcaneal impingement due to insertional tendon enlargement may occur, and prophylactic calcaneoplasty coupled with an insertional reattachment procedure could achieve promising postoperative outcomes for patients with insertional Achilles tendon rupture.